Disseminated blastomycosis. (2020) - Hashim, Samaher; Barrios, Christopher
Abstract: Blastomycosis is a fungal infection caused by Blastomyces dermatitidis, a dimorphic fungus endemic in the soils of the Ohio and Mississippi River Vallys, Great Lakes region, and southeastern United States. It most commonly manifests as a pulmonary infection following inhalation of spores, which causes a broad array of clinical manifestations ranging from asymptomatic infection to fulminant sepsis with acute respiratory distress syndrome and death. Extrapulmonary disease occurs in approximately 25–30% of patients following hematogenous spread from the lungs, with skin being the most common site of exytrapulmonary disease. Here we present a case of disseminated blastomycosis in a healthy 48 year old female.